STUDENTS’ NUMERACY SKILLS IN SOLVING MINIMUM COMPETENCY ASSESSMENT (MCA)-TYPE MATHEMATICS PROBLEMS: A CASE STUDY IN JUNIOR HIGH SCHOOL - Amami, Chintia Shalaza; Saefudin, Abdul Aziz; Sunanti, Titis (Journal of Authentic Research on Mathematics Education (JARME), 2025)
Numeracy skills is one of the abilities of students who use mathematics as a tool to solve problems in everyday life. Therefore, this research aims to analyze students' numeracy skills to solve the Minimum Competency Assessment (AKM) type mathematics problems. This research method is a case study in one of the state schools in Yogyakarta. The results of this research show that students' numeracy abilities in solving mathematics problems, especially AKM type questions, can be demonstrated from students' ability to understand facts, processes, concepts and procedures; ability to apply conceptual knowledge and understanding in solving mathematical problems in everyday life; and reasoning abilities in analyzing data and information, making conclusions, and expanding understanding. In general, students have numeracy skills in the advanced category with characteristics including students having basic mathematical concepts and having ideas for determining strategies for solving problems very well. Then, students are also able to reason in solving complex and non-routine problems based on their mathematical concepts. With this, it is hoped that students can use their numeracy skills to solve problems they encounter in daily life.Copyright © 2021UniversitasSiliwangi. All rights reserved.